The Influence of The Barcode Scanning Payment System on Customer Satisfaction in Buying and Selling Transactions in Indonesia and India - Saputra, Achbar Adi; Aryani, Dwi Nita; Gahlaut, Ritika; Hui, Lim Sheue; Aggarwal, Reetika; Sattar, Nahian; Shiyas, Mohammed (International Journal of Applied Business and International Management, 2024)
This research  aims to test and analyze the effect of barcode scanning payment systems on customer satisfaction in Indonesia and India. The barcode scanning payment system in question is a barcode scanning payment system that exists in countries in Asia (for example Indonesia and India). These barcode scanning payment systems include QRIS in Indonesia, BharatQR and UPI QR in India, and many more. This study is quantitative research. Data is collected by distributing questionnaires to respondents from countries in India (50 responden) and Indonesia (57 responden) with a total of 107 respondents. The results of this study will be analyzed using SPSS application. In addition, this research is expected to provide final results in the form of a positive influence between the use of barcode scanning payment systems on customer satisfaction. The results will enrich the customer satisfaction theory, and give fruitful suggestions for financial regulators.